Development of a Bouyancy Control Device for Autonomous Underwater Vehicle - Lia Safiyah binti Syafie
The development of Autonomous Underwater Vehicle (AUV) which known as unmanned underwater vehicle increased exponentially in these recent years. This is due to the increase of demand in underwater vehicle applications such as prospecting on the seafloor and other underwater tasks without human interference and supervision. This vehicle can be used to perform underwater missions such as surveys, monitoring, image capturing and other applications. In achieving given tasks, AUVs must be capable to control its depth level. Depth level of the AUVs are mainly controlled either using thrust from propellers or varying buoyancy force on the AUVs through the control of buoyancy force using a device called Buoyancy Control Device (BCD). BCDs use the concept of varying mass by inserting air, water or paraffin wax to the chamber or ballast tank or by varying the volume of the ballast tank. This research is focusing in developing a volume based BCD for controlling the depth level of AUVs. A pair of rubber bellow is used to vary the volume of BCD while retaining its mass constant. The method used to vary the volume is by extending and retracting the bellow to vary the total volume of the BCD. With the change of volume, the buoyancy force of the BCD is varied against the gravitational force. Variation of buoyancy force will determine whether the BCD is experiencing negative buoyancy or positive buoyancy which results in submerging and rising of the BCD. The performance of the BCD is evaluated based on the volume change against the depth level achieved. The BCD is controlled manually for its full extension, partial extension and full retraction. The performance of the system is limited to a certain depth level change due to the design of the bellow.